Technical report: Using Vietnam’s National Nutrition Surveillance (NNS) survey to explore the relationship between human mobility and food and nutrition security in the Mekong Delta - Vaselli, Alessandra; Nguyen, Tam Ninh; Savelli, Adam; Duong, Thanh Thi; Tuan, Phuong Thi Mai; Truong, Mai Tuyet; Huynh, Tuyen (2024)
The CGIAR Research Initiatives on Asian Mega-Deltas, Climate Resilience, and Fragility, Conflict, and Migration have partnered with the Vietnam National Institute of Nutrition (NIN) to advance impactful research for food and nutrition security in Vietnam’s Mekong Delta (VMD). The collaboration unites CGIAR’s research activities on nutrition-sensitive, climate-resilient deltaic development planning with NIN’s remit to support food and nutrition security throughout Vietnam. Through localized-, demand-driven research, the partnership aims to support the achievement of The National Nutrition Strategy for 2021-2030 by integrating human mobility components into NIN’s yearly National Nutrition Surveillance (NNS) survey. At the core of this project is an acknowledgement of the complex relationship between food and nutrition security (FNS) and mobility outcomes in Vietnam’s Mekong Delta (VMD). With an eye toward the evidence gap related to the human mobility-FNS nexus in the VMD, The Alliance and NIN have co-developed a list of key indicators, which were then validated through participatory workshops with local stakeholders and NIN experts in charge of implementing the NNS. An integrated survey is expected to bolster national efforts to achieve inclusive food and nutrition security in line with UN Sustainable Development Goal 2: “Zero Hunger.”